Bothrops diporus (southern pitviper/Chaco Lancehead) : Diet / Ophiophagy - Ruiz Garcia, José Augusto (2018)
Bothrops diporus is a medium-sized pitviper found in southern Brazil, southern Paraguay, northern Argentina, and probably extreme south-central Bolivia. It feeds on a wide diversity of prey, including rodents, frogs, and lizards (Yanosky et al. 1996. Herpetol. Nat. Hist. 4:97–110; Giraudo et al. 2008. Revista FABICIB 12:69–89), and also sometimes on snakes (e.g., Erythrolamprus poecilogyrus, Chironius maculoventris; Giraudo et al., op. cit.; Barros and Waller 2015. Herpetol. Rev. 46: 443–444).